Opening the Gates of Our Being: Charting a Way Out of Fear with Jean Vanier and Emmanuel Mounier - Murphy, Thomas N. (Journal of disability & religion, 2020)
This essay draws the work of Jean Vanier and Emmanuel Mounier into dialogue, primarily on the topic of moving from a society built on fear to one built on love and communion. To accomplish this, the essay articulates aspects of Mounier's personalist philosophy and the influence thereupon of Nikolai Berdyaev. Texts similarly titled Be Not Afraid by Vanier and Mounier provide a jumping off point for the dialogue between their works. Finally, the essay casts Vanier's "way of the heart" as an expression of practical personalism.